2010
DOI: 10.1111/j.1365-2966.2010.17040.x
|View full text |Cite
|
Sign up to set email alerts
|

Compact binaries in star clusters - I. Black hole binaries inside globular clusters

Abstract: We study the compact binary population in star clusters, focusing on binaries containing black holes, using a self-consistent Monte Carlo treatment of dynamics and full stellar evolution. We find that the black holes experience strong mass segregation and become centrally concentrated. In the core the black holes interact strongly with each other and black hole-black hole binaries are formed very efficiently. The strong interactions, however, also destroy or eject the black hole-black hole binaries. We find no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
178
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 55 publications
(142 reference statements)
12
178
1
2
Order By: Relevance
“…This result also agrees with results of Downing et al (2010) [111] who used a similar-sized Monte Carlo dataset, primarily to study black hole-black hole binaries, and found no DNSs in any of their simulations. That DNSs are not produced in similar numbers to X-ray binaries in globular clusters may be a combination of the lower number of potential progenitors, kicks for both progenitors, and the likelihood of merging or producing a WD during interactions.…”
Section: Dynamical Evolutionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result also agrees with results of Downing et al (2010) [111] who used a similar-sized Monte Carlo dataset, primarily to study black hole-black hole binaries, and found no DNSs in any of their simulations. That DNSs are not produced in similar numbers to X-ray binaries in globular clusters may be a combination of the lower number of potential progenitors, kicks for both progenitors, and the likelihood of merging or producing a WD during interactions.…”
Section: Dynamical Evolutionsupporting
confidence: 91%
“…The Monte Carlo simulations of Downing et al 2010 and 2011 [111, 112] and the direct N -body simulations of Banerjee et al 2010 [28]. Downing et al used the Monte Carlo code of Giersz [153, 155] to perform 160 fully self-consistent simulations of globular clusters with 500,000 particles, a realistic mass function, stellar evolution, 10–50% primordial binaries, and various combinations of initial concentration and metallicity.…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…Although many channels have been explored for the formation of such systems, most proposals fall into two categories: the "field" channel, in which BBHs are formed from isolated stellar binaries, usually involving either a common-envelope phase (e.g., Voss & Tauris 2003;Dominik et al 2012Dominik et al , 2013Belczynski et al 2016) or chemically homogeneous evolution due to rapid stellar rotation (e.g., De Mink & Mandel 2016;Marchant et al 2016), or the "dynamical" channel, in which BBHs are created though three-body encounters in dense star clusters (e.g., Sigurdsson & Hernquist 1993;Portegies Zwart & Mcmillan 2000;Downing et al 2010Downing et al , 2011Ziosi et al 2014;Rodriguez et al 2015Rodriguez et al , 2016a. Unfortunately, the masses and merger rates predicted by these models often significantly overlap, making it difficult to discriminate between different formation channels for BBHs even with multiple detections.…”
Section: Introductionmentioning
confidence: 99%
“…The starting point of our work are Monte Carlo cluster simulations, developed by Downing et al (2010), providing a realistic description of a typical GC with initial number of particles of 2 × 10 6 drawn from a Plummer (1911) model, a Kroupa (2001) initial mass function, 10% primordial binary fraction, and metallicity [Fe/H]=-1.3. The simulations have no central IMBH and no internal rotation (note however that internal rotation is observed in several GCs, e.g.…”
Section: Constructing a Mock Ifu Observationmentioning
confidence: 99%